2010
DOI: 10.1007/s10354-010-0829-7
|View full text |Cite
|
Sign up to set email alerts
|

Opiate sparing effect of fixed combination of diclophenac and orphenadrine after unilateral total hip arthroplasty: A double-blind, randomized, placebo-controlled, multi-centre clinical trial

Abstract: Multimodal pain management combines analgesics to improve analgesia and reduce side effects. This study investigates the fixed combination of diclophenac and orphenadrin (Neodolpasse(®) Infusion Solution) in patients after unilateral total hip arthroplasty (THA). This prospective, randomized, double-blind, placebo-controlled, multi-centre clinical study enrolled 120 patients receiving patient-controlled analgesia (PCA). Isotonic saline was infused as placebo. The primary efficacy goal was defined as reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Regular i.v. diclofenac and orphenadrine infusions after surgery and at 12 h reduced morphine patient‐controlled analgesia (PCA) consumption postoperatively [22]. McQuay et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular i.v. diclofenac and orphenadrine infusions after surgery and at 12 h reduced morphine patient‐controlled analgesia (PCA) consumption postoperatively [22]. McQuay et al.…”
Section: Resultsmentioning
confidence: 99%
“…Regular i.v. diclofenac and orphenadrine infusions after surgery and at 12 h reduced morphine patient-controlled analgesia (PCA) consumption postoperatively [22]. McQuay et al [23] showed that a combination of oral dexketoprofen 25 mg with tramadol 75 mg was superior to both medications alone for postoperative pain control.…”
Section: Basic Systemic Non-opioid Analgesicsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included trials were conducted in adult populations aged 18 years or older, and 1 study was conducted specifically in a geriatric population over 65 years of age. 19 All studies were conducted in the surgical setting, and common surgeries in the trials reviewed included gynecologic surgery/cesarean delivery (n = 15), 12,13,18,[20][21][22][23][24][25][26] orthopedic/arthroscopic surgery (n = 10), 11,14,19,[27][28][29][30][31][32][33] and spinal surgery (n = 4). [34][35][36][37] Findings from individual NSAIDs are presented below.…”
Section: Resultsmentioning
confidence: 99%
“…A number of different agents and modalities have been studied as alternative pain therapies, including local or regional nerve blocks, acetaminophen, gabapentin, and nonsteroidal anti-inflammatory drugs (NSAIDs). In particular, NSAIDs have shown promise at maximizing analgesia while decreasing the opioid-related side effects and addiction risk [15][16][17][18][19][20]. Additionally, intravenous (IV) preparations have the benefit of greater bioavailability than oral medication for patients in need of acute pain management [21,22].…”
Section: Introductionmentioning
confidence: 99%